Comparative Numeracy in Statistical Reasoning of Pre-Service Early Childhood Teachers - Dina Apryani; Elce Purwandari; Annisa Yulistia; Rafiq Badjeber; Chika Rahayu; Maya Adina Pratama (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
This study aims to analyze differences in statistical reasoning and numeracy skills between two groups of PG-PAUD Study Program students. Using a quantitative comparative approach, all 49 PG-PAUD students enrolled in statistics during the 2025/2026 even semester were included, divided into class A (25 students) and class B (24 students). The second group used IBM SPSS Statistics and the VClass platform for equivalent learning. Data were obtained through a digital-based final semester exam with 25 multiple-choice questions assessing statistical reasoning. Data analysis included normality and homogeneity tests, followed by an independent sample t-test and effect size analysis using Cohen’s d with IBM SPSS Statistics at a significance level of 0.05. Results show no significant difference in numeracy abilities in statistical reasoning between classes (t = 1.295; sig. = 0.201 > 0.05; Cohen's d = 0.37). Although class A had a higher average score (M = 81.28; SD = 13.99) compared to class B (M = 76.00; SD = 14.54), this difference was not statistically significant, and the effect size was small. Indicator analysis highlighted that students excelled most in selection analysis, but scored lower in understanding concepts, interpreting, and drawing conclusions. These findings underscore that while technology-based learning yields comparable statistical reasoning results, there is still room for deeper skill development